2015
DOI: 10.4300/jgme-d-14-00315.1
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Formal Mentorship Program for Internal Medicine Residents: Can We Facilitate Genuine Mentorship?

Abstract: Background Mentorship programs are perceived as valuable, yet little is known about the effect of program design on mentoring effectiveness. Intervention We developed a program focused on mentoring relationship quality and evaluated how subsequent relationships compared to preexisting informal pairings. Methods Faculty members were invited by e-mail to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…The program's framework included voluntary faculty participation, active mentee choice in the pairing, mentee role understanding, facilitated mentorship meetings, and deliberate relationship reviews. 13,15,16 Mentorship programs for individual training programs have shared similar foundations, including adequate training of mentors, protected mentorship time, and structured expectations to encourage accountability. Common limitations of these individual training models include absence of comparison groups, insufficient survey metrics, and lack of measures of long-term sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The program's framework included voluntary faculty participation, active mentee choice in the pairing, mentee role understanding, facilitated mentorship meetings, and deliberate relationship reviews. 13,15,16 Mentorship programs for individual training programs have shared similar foundations, including adequate training of mentors, protected mentorship time, and structured expectations to encourage accountability. Common limitations of these individual training models include absence of comparison groups, insufficient survey metrics, and lack of measures of long-term sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The debate between organic versus assigned mentors is long standing and research exists highlighting the benefits of both. 40 43 Our results demonstrated that there was not a significant difference in resident satisfaction or mentorship effectiveness based on program type or if a mentor was assigned versus self-selected. In addition, residents favored having a mentorship program.…”
Section: Discussionmentioning
confidence: 70%
“… 23 Previous research has shown the prevalence of mentorship rises to 77 – 90% when mentorship programs are in place. 17 , 40 In the interviews, program directors appeared reluctant to accept mentorship programs, as they believed it negates the ability to form organic mentorship. The debate between organic versus assigned mentors is long standing and research exists highlighting the benefits of both.…”
Section: Discussionmentioning
confidence: 99%
“…2,11,12 Mentors should be adequately trained to fulfill the agreed roles. [13][14][15][16] With this framework, both mentee and mentor can significantly benefit from the relationship. 3,5 Individualization and flexibility of the MAC faculty-mentee relationship enhanced participants' experiences and improved participation.…”
Section: Discussionmentioning
confidence: 99%